A New Species of Tarantula Spider in the Genus Lyrognathus Pocock 1895 (Araneae, Theraphosidae) from Sumatra. (17th April 2013) - Nunn, Steven C.; West, Rick C.
Abstract : A new species is described in the tarantula genus Lyrognathus Pocock 1895, being the first record of this taxon from Sumatra, Indonesia. Lyrognathus giannisposatoi sp. nov. is also unique in its habitat selection, being the first confirmed lowland species from this genus. A new key to Lyrognathus species is provided, and a biogeography of the group is briefly discussed.